CKD in diabetes: diabetic kidney disease versus nondiabetic kidney disease - Anders, Hans-Joachim; Huber, Tobias B; Isermann, Berend; Schiffer, Mario (Nature reviews. Nephrology, 2018)
The increasing global prevalence of type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) has prompted research efforts to tackle the growing epidemic of diabetic kidney disease (DKD; also known as diabetic nephropathy). The limited success of much of this research might in part be due to the fact that not all patients diagnosed with DKD have renal dysfunction as a consequence of their diabetes mellitus. Patients who present with CKD and diabetes mellitus (type 1 or type 2) can have true DKD (wherein CKD is a direct consequence of their diabetes status), nondiabetic kidney disease (NDKD) coincident with diabetes mellitus, or a combination of both DKD and NDKD. Preclinical studies using models that more accurately mimic these three entities might improve the ability of animal models to predict clinical trial outcomes. Moreover, improved insights into the pathomechanisms that are shared by these entities - including sodium-glucose cotransporter 2 (SGLT2) and renin-angiotensin system-driven glomerular hyperfiltration and tubular hyper-reabsorption - as well as those that are unique to individual entities might lead to the identification of new treatment targets. Acknowledging that the clinical entity of CKD plus diabetes mellitus encompasses NDKD as well as DKD could help solve some of the urgent unmet medical needs of patients affected by these conditions.